(untitled) (Research, Society and Development, 2024)
The aim of the present study was to search for the main cardiovascular complications presented by patients affected by COVID-19 and to identify the nursing diagnoses related to these complications. This is an integrative literature review, one of the methods of knowledge synthesis through a systematic and rigorous process, prepared in accordance with the PRISMA Statment recommendations to answer the following question: what are the cardiovascular complications in patients affected by COVID -19 and the related nursing diagnoses? Four articles were selected that answered the guiding question, where the main cardiovascular complications were raised, relating them to Nursing Diagnoses from the NANDA-I Taxonomy, with six Nursing diagnoses being extracted to guide the Nurse’s assistance in these cases.